2012
DOI: 10.1159/000339245
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Medium from Bone Marrow Mesenchymal Stem Cells Transiently Retards Osteoblast Differentiation by Downregulating Runx2

Abstract: Mesenchymal stem cells (MSCs) are attractive candidates for cell therapy and regenerative medicine because of their potential for proliferation and multilineage differentiation. MSCs secrete various cytokines, acting as trophic mediators to regulate neighboring cells. Osteoblasts are the cells directly responsible for forming new bone, and they are the final target of many osteogenic regulators. However, the induction effect of MSCs on osteoblasts is still unknown. In this study, we isolated osteoblasts from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 74 publications
3
30
1
2
Order By: Relevance
“…ALP is an early osteoblast marker and Runx2 is a critical transcription factor for osteoblastic differentiation [22], [23], We found that hyperglycemia interfered with the differentiation of rat osteoblasts, and glimepiride increased the expression of these marker genes at two different glucose concentrations. However, we showed that inhibition of PI3K P85 by LY294002 reduced ALP, Runx2 and OCN mRNA expression in osteoblasts.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…ALP is an early osteoblast marker and Runx2 is a critical transcription factor for osteoblastic differentiation [22], [23], We found that hyperglycemia interfered with the differentiation of rat osteoblasts, and glimepiride increased the expression of these marker genes at two different glucose concentrations. However, we showed that inhibition of PI3K P85 by LY294002 reduced ALP, Runx2 and OCN mRNA expression in osteoblasts.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, we extracted mRNA from both groups of osteoblasts cultured with basic media containing 5.5 mM or 16.5 mM glucose for 7 days and performed real-time PCR to determine the expression levels of osteoblast marker genes, including Runx2 (Runt-related transcription factor 2) (Fig. 4A), a critical transcription factor for osteoblastic differentiation [23], and ALP (Fig. 4B), an early osteoblast marker [24].…”
Section: Resultsmentioning
confidence: 99%
“…differences in Runx2 expression in these cells. Another reason for the differences in Runx2 expression may be due to fluctuations of Runx2 during the cell cycle [50]. It has been shown that proliferating cells may contain more Runx2 [49].…”
Section: Figmentioning
confidence: 99%
“…However, experimental evidence from other laboratories provided evidence that a transient serum deprivation before induction of differentiation, which also causes a retardation of proliferation, could facilitate the differentiation of MSC in vitro [53]. In addition, supernatants from MSC transiently suppressed maturation of osteoblasts by downregulating expression of Runx2 [50]. Therefore, differences in the release of osteogenic factors from bmMSC in primary culture or during initiation of differentiation could account for their prominent osteogenic potential.…”
Section: Figmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are an appealing candidate for tissue regeneration due to their ability to differentiate into many cell types (1). However, the use of stem cells has several problems such as complicated safety and quality management and high cost and difficult cell handling (2).…”
mentioning
confidence: 99%